2006
DOI: 10.1002/cpp.507
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate mind training for people with high shame and self‐criticism: overview and pilot study of a group therapy approach

Abstract: Compassionate mind training (CMT) was developed for people with high shame and self-criticism, whose problems tend to be chronic, and who find self-warmth and self-acceptance difficult and/or frightening. This paper offers a short overview of the role of shame and self-criticism in psychological difficulties, the importance of considering different types of affect system (activating versus soothing) and the theory and therapy process of CMT. The paper explores patient acceptability, understanding, abilities to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

67
1,137
3
67

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,374 publications
(1,274 citation statements)
references
References 81 publications
67
1,137
3
67
Order By: Relevance
“…Lateral OFC (BA 47) activation was also found to positively correlate with high RS scores for the self-critical condition, suggesting that additional recruitment of inhibitory control processes was instigated during self-critical thoughts in these individuals. This finding could be used as evidence to help build towards improved targeting in psychotherapy, as focused therapeutic exercises designed to develop self-reassurance may aid regulation in the face of setbacks (Gilbert and Procter, 2006;Gilbert, 2009).…”
Section: Multiple Regression With Reassured Self (Rs) and Inadequatementioning
confidence: 99%
See 1 more Smart Citation
“…Lateral OFC (BA 47) activation was also found to positively correlate with high RS scores for the self-critical condition, suggesting that additional recruitment of inhibitory control processes was instigated during self-critical thoughts in these individuals. This finding could be used as evidence to help build towards improved targeting in psychotherapy, as focused therapeutic exercises designed to develop self-reassurance may aid regulation in the face of setbacks (Gilbert and Procter, 2006;Gilbert, 2009).…”
Section: Multiple Regression With Reassured Self (Rs) and Inadequatementioning
confidence: 99%
“…The ability to be selfreassuring in the face of setbacks is believed to be the result of both temperament and early attachment experiences (Mikulincer and Shaver, 2007) and result in resilience (Masten, 2001). Furthermore, new developments in psychotherapy are beginning to focus on the possibility of training people in self-reassurance and self-compassion with beneficial effects (Gilbert and Irons, 2005;Gilbert and Procter, 2006;Leary et al, 2007;Lutz et al, 2008). Gilbert (1989Gilbert ( , 2000 and Gilbert and Irons (2005) suggested that self-criticism and self-reassurance may stimulate the same neurophysiological systems as criticism and reassurance generated externally, i.e., by others.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that increasing positive beliefs about the self has an indirect effect on negative beliefs, but the implication of the present findings is that explicitly targeting negative beliefs might bring about symptom benefits more directly. One example of a psychological intervention that might achieve therapeutic effects by breaking down negative self-evaluations is Compassionate Mind Training (Gilbert & Procter, 2006).…”
Section: Depression-related Interventions For People With Psychosismentioning
confidence: 99%
“…Primary outcome measures were changes in assessment scores of HDRS 17 and GAF, 12 from baseline to 6, 12, and 18 months, with a prespecified primary outcome assessment at 6 months and 12 months. However, the original protocol allowed SDS treatment for longer than 12 months so that planned transfer of care could be graduated for up to 3 months for these patients, from the SDS to a primary or secondary mental health clinical team.…”
Section: Discussionmentioning
confidence: 99%
“…When clinically indicated, the psychological interventions were augmented as part of relapse prevention (within the timeframe of the overall intervention) with mindfulness-based cognitive therapy. 16 Additionally, when the clinical presentations identified high levels of shame and self-criticism, compassion-focused therapy 17 integrated within a CBT framework was used as part of relapse prevention. Further, when clinically indicated, social inclusion initiatives were used in the context of CBT, which included vocational-based and occupational-based activities.…”
Section: Methodsmentioning
confidence: 99%